Application of Value Management by Real Estate Development Practitioners: A Review of Enticing Factors - Yeptadian Sari; Lutfi Prayogi (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
The application of a method in real estate development is needed in order to ensure the project runs smoothly. There are methods that can increase the value of the project and even discard the unnecessary cost of the project called value management (VM). This research is an exploratory research applying inferential statistics using exploratory factor analysis. Factor analysis is used to discover the benefits of VM practices that are correlated between each indicator which makes real estate development practitioners interested to apply VM. The sample taking and respondent determination are applied by a purposive sampling followed by snowball sampling. Data collection techniques use a survey by distributing the questionnaires. There are five benefits that can make practitioners interested in applying VM, the benefits are to identified objectives, needs and project constraints; VM can produce the best designs; VM is capable of deciding on the best project completion; VM facilitating interaction between designers; VM is the method to get the cost effectiveness of real estate development.